Gastrointestinal Stromal Tumor – An Evolving Concept - Tornillo, Luigi (Frontiers in Medicine, 2014)
Gastrointestinal stromal tumors are the most frequent mesenchymal tumors of the gastrointestinal tract. The discovery that these tumors, formerly thought of smooth muscle origin, are indeed better characterized by specific activating mutation in genes coding for the receptor tyrosine kinases CKIT and PDGFRA and that these mutations are strongly predictive for the response to targeted therapy with receptor tyrosine kinase inhibitors has made GISTs the typical example of the integration of basic molecular knowledge in the daily clinical activity. The information on the mutational status of these tumors is essential to predict (and subsequently to plan) the therapy. As resistant cases are frequently wild-type, other possible oncogenic events, defining other “entities”, have been discovered (e.g. succinil dehydrogenase mutation/dysregulation, insuline growth factor expression, mutations in the RAS-RAF-MAPK pathway). The classification of disease must nowadays rely on the integration of the clinico-morphological characteristics with the molecular data.